Alterations of bone mineral density, bone microarchitecture and strength in patients with ankylosing spondylitis: a cross-sectional study using high-resolution peripheral quantitative computerized tomography and finite element analysis. Issue 1 (December 2015) - Nigil Haroon, Nisha; Szabo, Eva; Raboud, Janet; Mcdonald-Blumer, Heather; Fung, Lydia; Josse, Robert; Inman, Robert; Cheung, Angela
Abstract Introduction Ankylosing spondylitis (AS) is an inflammatory disease associated with new bone formation and an increased risk of osteoporosis and fractures. The negative effects of AS on bone microarchitecture and strength are unclear. Thus, we conducted an observational study to analyze the effect of AS on bone microarchitecture and strength. Methods Patients with AS (n = 53) and non-AS subjects (n = 85) were recruited for the study. All subjects underwent clinical evaluation, DXA and high-resolution peripheral quantitative CT scans (HRpQCT). Results The AS patients were aged 44 ± 12 (mean ± standard deviation) years and had a median disease duration of 17 (interquartile range: 7–27) years. They were found to have lower cortical, trabecular and total vBMD at the distal radius and tibia than non-AS subjects on multivariable regression analysis. Cortical parameters such as cortical thickness and porosity, and bone strength parameters such bone stiffness and stress as estimated by finite element analysis (FEA) in AS patients were significantly worse than that of-non-AS subjects. Among patients with AS, male sex, mSASSS greater than zero and HLA-B27 negative status were associated with worse bone microarchitecture. Conclusions Patients with AS have worse bone mineral density, microarchitecture and strength when compared to non-AS subjects. More research is needed to understand the mechanisms underlying bone pathology in AS and to assess the effect of treatments such as TNF inhibitors on bone quality and fracture risk.